PENYULUHAN MASALAH STUNTING TERKAIT PENCEGAHAN MASALAH DAN MASA DEPAN INDONESIA - Hastuti, Wedia; Dulame, Irma Maria (Publika Citra Media, 2024)
Stunting is a growth disorder in children caused by repeated infections and malnutrition. This is indicated by the child's height being less than the age standard. The stunting rate in Indonesia is still quite high. Although there is a decrease from 24.4 percent in 2021 to 21.6 percent in 2022, this figure is still far from the target of 14% in 2024. Long-term malnutrition which can start during pregnancy is the main cause of stunting. Therefore, it is very important to consider the nutritional intake of pregnant and breastfeeding mothers, and provide appropriate complementary foods for breast milk. To prevent stunting, pregnant women must get better nutrition, get the right complementary foods for breast milk, and encourage eating healthy foods. The Indonesian government, in collaboration with international organizations such as UNICEF, has taken various steps to address this problem. The method used in this community service activity consists of several stages, namely the preparation stage, implementation stage and evaluation stage. This activity was carried out at Posyandu Sejahtera Pondok Kelapa Duren Sawit, East Jakarta. The results of the counseling showed that as a result of the implementation of community service, 90% of theparticipants were able to explain stunting prevention.